МЕТОД СИНХРОННОЙ ШИРОТНО-ИМПУЛЬСНОЙ МОДУЛЯЦИИ ПРИМЕНИТЕЛЬНО К УПРАВЛЕНИЮ ЧЕТЫРЬМЯ ИНВЕРТОРАМИ НАПРЯЖЕНИЯ, ПИТАЮЩИМИ АСИММЕТРИЧНЫЙ ШЕСТИФАЗНЫЙ АСИНХРОННЫЙ ЭЛЕКТРОДВИГАТЕЛЬ - Олещук, В.; Сизов, А. (Інститут електродинаміки НАН України, Київ, 2011)
Novel method of space-vector-based pulsewidth modulation (PWM) has been disseminated for synchronous control of four inverters feeding six-phase drive on tire base of asymmetrical induction motor which has two sets of windings spatially shifted by SO electrical degrees. Basic schemes of synchronized PWM, applied for control of four separate voltage source inverters, allow both continuous phase voltages synchronization in the system and required power sharing between DC-sources. Simulations show a behavior of six-phase system with continuous and discontinuous versions of synchronized PWM. References 19, table 1, figures 7.